EP226/#923 Economic burden in platinum-resistant ovarian cancer. (4th December 2022) - Indukuri, Nikhila; Musat, Mihaela; Chavez, Gordon; Proescholdt, Christina
Abstract : Objectives: Introduction Platinum-resistant ovarian cancer (PROC) is associated with a substantial economic burden. An economic SLR was conducted to evaluate the economic burden and cost-effectiveness analyses (CEA) of therapies used in advanced ovarian cancer resistant or refractory to platinum-based chemotherapy. Methods: The scope of the SLR was defined using the Patient population, Intervention, Comparators, Outcomes measures and Study design (PICOS) statement, and performed in accordance with PRISMA guidelines. Medical Literature Analysis and Retrieval System Online [MEDLINE®] and Excerpta Medica Database [Embase®], EconLit and Cochrane were searched for records dated up to the search date of July 6, 2021. Relevant congresses (2017–2021), previous HTA submissions, and bibliographies of previously conducted SLRs were searched to capture all relevant data. Results: Seventeen publications out of 1, 092 records from the Ovid search were deemed relevant for the analysis. Of 17 included studies, 12 were CEAs and 5 were observational studies evaluating cost and healthcare resource use in US, Iran, Canada, Belgium, Spain, Thailand, Portugal, and Australia. Healthcare costs for ovarian cancer increase with disease progression to more advanced stages of disease and by increased lines of chemotherapy treatment. The average annual per patient cost was €24, 111, increasing from €8, 641 in stage I to €42, 547 in stage IV. Advanced chemotherapy, hospitalizations, and surgery accounted for 87.2% of direct healthcare costs (Delgado-Ortega et al. 2019). Indirect costs were estimated at €1, 002 per patient annually. Conclusions: Conclusion There is a need for more affordable and tolerable treatment options for patients with ovarian cancer resistant or refractory to platinum-based chemotherapy.